Ten-year results of the PORTEC-2 trial for high-intermediate risk endometrial carcinoma: improving patient selection for adjuvant therapy. Issue 9 (30th October 2018) - Wortman, B.; Creutzberg, C.; Putter, H.; Jürgenliemk-Schulz, I.; Jobsen, J.; Lutgens, L.; Steen-Banasik, E.; Mens, J.; Slot, A.; Kroese, M.; Triest, B.; Nijman, H.; et al.
Abstract Background PORTEC-2 was a randomised trial for women with high-intermediate risk (HIR) endometrial cancer, comparing pelvic external beam radiotherapy (EBRT) with vaginal brachytherapy (VBT). We evaluated long-term outcomes combined with the results of pathology review and molecular analysis. Methods 427 women with HIR endometrial cancer were randomised between 2002–2006 to VBT or EBRT. Primary endpoint was vaginal recurrence (VR). Pathology review was done in 97.4%, combined with molecular analysis. Results Median follow-up was 116 months; 10-year VR was 3.4% versus 2.4% for VBT vs. EBRT (p  = 0.55). Ten-year pelvic recurrence (PR) was more frequent in the VBT group (6.3% vs. 0.9%, p  = 0.004), mostly combined with distant metastases (DM). Ten-year isolated PR was 2.5% vs. 0.5%, p  = 0.10, and DM 10.4 vs. 8.9% (p  = 0.45). Overall survival for VBT vs. EBRT was 69.5% vs. 67.6% at 10 years (p  = 0.72). L1CAM and p53-mutant expression and substantial lymph-vascular space invasion were risk factors for PR and DM. EBRT reduced PR in cases with these risk factors. Conclusion Long-term results of the PORTEC-2 trial confirm VBT as standard adjuvant treatment for HIR endometrial cancer. Molecular risk assessment has the potential to guide adjuvant therapy. EBRT provided better pelvic control in patients with unfavourable risk factors.